Clinical and vascular lesion characteristics of the patients with takayasu arteritis manifested firstly as acute myocardial infarction at onset - Ruifang Liu; Fangxing Xu; Yujie Zhou; Dongmei Shi; Tongku Liu (Heliyon, 2023)
Objective: To explore clinical and vascular lesion characteristics of the patients with Takayasu arteritis (TA) manifested firstly as acute myocardial infarction (AMI) at onset and to improve the diagnostic rate of TA. Methods: The clinical and angiographic data of six patients with TA manifested firstly as AMI at onset were retrospectively analyzed. Results: Of six patients (16–25 years old), 83.33% (five cases) was female, three patients had a history of hypertension and three patients did not have any medical history. One patient had intermittent effort chest tightness. On admission patients all presented with chest pain, dyspnea, hypotension, cardiogenic shock, abnormal electrocardiogram, and elevated cardiac troponin I. The vessel involvement was left coronary main trunk 83.33%, left anterior descending artery 33.33% and left circumflex branch 16.67%, right coronary artery 66.67%, subclavian artery 83.33%, and renal artery 50%. Five patients received the emergency PCI. One patient died of heart failure. During follow-up 3 patients received again PCI treatment. Conclusion: Clinical and vascular lesion characteristics of those patients were no discomfort before admission, and the suddenly typical manifestation of AMI. Severe stenosis or occlusion occurred in main coronary artery ostia and peripheral large artery. For the TA patients with hemodynamic instability the effectiveness of emergency PCI is positive.